2016
DOI: 10.3389/fmicb.2016.01323
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Phase, pH, and Temperature on the Abundance and Composition of Tetraether Lipids in the Thermoacidophile Picrophilus torridus

Abstract: The abundance and composition of glycerol dibiphytanyl glycerol tetraether (GDGT) and glycerol tribiphytanyl glycerol tetraether (GTGT) lipids were determined as a function of growth phase as a proxy for nutrient availability, the pH of growth medium, and incubation temperature in cultures of the thermoacidophile Picrophilus torridus. Regardless of the cultivation condition, the abundance of GDGTs and GTGTs was greater in the polar than core fraction, with a marked decrease in core GDGTs in cultures harvested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 63 publications
(119 reference statements)
7
60
2
Order By: Relevance
“…When pH deviated from the optimum pH of ∼3 for DSM639, cyclization decreased. Whereas prior thermoacidophile studies showed that cyclization primarily decreased with increases in pH (10, 11, 25), we observed decreased cyclization when the pH was both above and below optimal. Despite the similarity in RI values at pH 2 and pH 4, the composition of GDGTs at each pH also was distinct (Figure 2, Figure 5).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…When pH deviated from the optimum pH of ∼3 for DSM639, cyclization decreased. Whereas prior thermoacidophile studies showed that cyclization primarily decreased with increases in pH (10, 11, 25), we observed decreased cyclization when the pH was both above and below optimal. Despite the similarity in RI values at pH 2 and pH 4, the composition of GDGTs at each pH also was distinct (Figure 2, Figure 5).…”
Section: Discussioncontrasting
confidence: 94%
“…Growth rate and ring index broadly covary, independent of which variable is causing this forcing (Figure 4). The temperature, pH and shaking speed experiments show inverse trends between growth rate and RI, consistent with batch experiments in the existing Thaumarchaeota (Figure S1) and Crenarchaeota (Figure S2) literature (11, 12, 29). However, these trends directly oppose results from other experiments characterizing GDGT response to pH in thermoacidophiles (11).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The high abundances of GTGTs in HWCG-III Thaumarchaeota are unprecedented among cultivated archaea (Table 2; cf. De Rosa and Gambacorta, 1988;Knappy et al, 2011;Feyhl-Buska et al, 2016) and have previously been interpreted to reflect sub-optimal growth conditions of Ca. N. yellowstonii (cf.…”
Section: Chemotaxonomic Characteristics Of the Thaumarchaeal Lipidomementioning
confidence: 99%
“…The lowest pHmin -0.06 was observed for two hyperacidophilic Archaea known as Picrophilus oshimae and P. torridus (pHopt 0.7), isolated from a solfataric hot spring in Noboribetsu (Hokkaido, Japan) (Schleper et al, 1996). These heterotrophic and aerobic polyextremophiles can also withstand temperatures of up to 65ºC (Topt = 60ºC, Tmin = 47ºC), potentially through increased cyclization of their tetraether membrane lipids as a generalized response to pH, temperature, and nutrient stress (Feyhl-Buska et al, 2016). In comparison to extreme acidophily, the highest pHmax of 12.5 was observed for an alkaliphilic, aerobic, mesophilic bacterium known as Serpentinomonas sp.…”
Section: Parameters That Limit Lifementioning
confidence: 99%